DOI: 10.4018/978-1-60960-511-7.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Potential of Mobile Learning through SMS Text for Open and Distance Learners

Abstract: Malaysia has a population of about 28 million people but there are, incredibly, more than 30 million mobile phone subscriptions. Sixth in the world in terms of SMS (Short Message Service) volume, Malaysians appear to be addictive SMS texters. With over 98 percent of its students having mobile phones and 82 percent of the students ready for learning through mobile phones, Open University Malaysia initiated a project that first experimented with podcasts and SMS texts later. This chapter describes how the instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…While, relating to this code, the participant coded R6:1 in Abu-Al-Aish et al 's (2012) study asserted, "This would enable students to study whilst they are out, for example, on trains and buses etc., and would be enormously helpful," the participant coded R9:1 in Nallliveettil and Alenazi's (2016) study stated, "Mobile phones are within our reach at any time, and we can use them without any time limit". Considering the quotes derived from the authors of primary studies, Abas et al (2009) have contended, "Mobile learning has the capacity to contribute to the flexibility of learning in ODL institutions. It can take learning right into the home, workplace and community.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While, relating to this code, the participant coded R6:1 in Abu-Al-Aish et al 's (2012) study asserted, "This would enable students to study whilst they are out, for example, on trains and buses etc., and would be enormously helpful," the participant coded R9:1 in Nallliveettil and Alenazi's (2016) study stated, "Mobile phones are within our reach at any time, and we can use them without any time limit". Considering the quotes derived from the authors of primary studies, Abas et al (2009) have contended, "Mobile learning has the capacity to contribute to the flexibility of learning in ODL institutions. It can take learning right into the home, workplace and community.…”
Section: Resultsmentioning
confidence: 99%
“…This code was mentioned by the participant coded R2:1 in Abas et al 's (2009) study, "We felt like we were so special, " and in Aish et al 's ( 2012) study, "The findings of the study show that students have a positive perspective of using M-learning and they look at it as a support system for traditional class based learning" (p. 1). Moreover, while the participant coded R2:2 in Abas et al's (2009) study mentioned the code it provides motivation as, "I think this [sic] kind of words really motivate," Donaldson (2011) has interpreted this situation in his study, "Comments from participants also suggest that the convenience of accessing information on a mobile device contributes to their enjoyment" (p. 113). Using mobile devices for content retrieval creates learning opportunities and increases student motivation (Ally et al, 2007;Mendez-Coca & Silisko, 2013).…”
Section: Beliefmentioning
confidence: 97%
See 1 more Smart Citation
“…The selection of mobile applications for language learning is significantly influenced by the features they offer. Abas et al (2009) observed that adult learners appreciate features such as events notifications, study tips, and learning modules with audio. This kind of approach to mobile learning is one that is tailored and one that takes into account the experience of adult learners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8 Also, smartphones can be used by the users at any time and from anywhere, which is a great advantage. 9 At present, smartphone applications (apps) are in the front line of the 4th wave of educational technologies 10 and are increasingly used for enhanced learning in dental and medical education. 5,11 Radiographic examination is necessarily required for accurate diagnosis of intrabony lesions.…”
Section: Introductionmentioning
confidence: 99%